Vascular phenotype at 35–37 weeks' gestation in women with gestational diabetes mellitus. (1st March 2023) - Mansukhani, T.; Arechvo, A.; Cecchini, F.; Breim, M.; Wright, A.; Nicolaides, K. H.; Charakida, M.
ABSTRACT: Objectives: To examine the vascular phenotype at 35–37 weeks' gestation of women with gestational diabetes mellitus (GDM) and compare it to that in women without GDM, using ophthalmic artery Doppler and carotid–femoral pulse‐wave velocity. Methods: This was a prospective observational study of women attending for a routine hospital visit at 35 + 0 to 37 + 6 weeks' gestation. This visit included recording of maternal demographic characteristics and medical history, ophthalmic artery Doppler for calculation of the peak systolic velocity (PSV) ratio and assessment of cardiac output, stroke volume, total peripheral resistance, central systolic and diastolic blood pressure, carotid–femoral pulse‐wave velocity and augmentation index. All measurements were standardized to remove the effects of maternal characteristics and elements from the medical history, and the adjusted values in the GDM group were compared with those in the non‐GDM group. Results: The study population of 2018 pregnancies contained 218 (10.8%) that developed GDM, including 78 (35.8%) that were treated with diet alone, 81 (37.2%) treated with metformin and 59 (27.1%) treated with insulin with or without metformin. In the GDM group, compared with the non‐GDM group, there were significantly higher ophthalmic artery PSV ratio, carotid–femoral pulse‐wave velocity and central systolic blood pressure, but there was no significant difference in cardiac output, stroke volume, total peripheral resistance, central diastolic blood pressure or augmentation index. In the GDM group, women treated with metformin or insulin had a higher ophthalmic artery PSV ratio compared with those treated with diet alone. Additionally, compared with the diet group, the metformin group had higher central systolic blood pressure and the insulin group had a higher carotid–femoral pulse‐wave velocity. Conclusion: Women with GDM have evidence of early vascular disease, and this may contribute to their long‐term cardiovascular risk. © 2022 International Society of Ultrasound in Obstetrics and Gynecology.